Genetic Diversity of Japonica Rice (Oryza sativa L.) Based on Markers Corresponding to Starch Synthesizing Genes - Lestari, Puji; Reflinur, (UI Scholars Hub, 2016)
Genes related to starch synthesis and the metabolism contribute to a variety of physicochemical properties that determine the eating/cooking qualities of rice. Our previous study suggested that a set of molecular markers was able to estimate the eating quality of japonica rice. The present study reports the genetic diversity of 22 japonica rice varieties based on markers corresponding to starch synthesizing genes. The mean of the polymorphic information content (PIC: 0.135) value and the diversity index (0.171) indicated a low genetic diversity in these varieties. The phylogenetic tree clearly demonstrated three main clusters: 1) cluster I contained seven varieties with similar physicochemical properties; 2) cluster II only showed a Japanese variety, Koshihikari, and 3) cluster III included the most Korean varieties (14 varieties). This phylogenetic analysis did not completely represent the physicochemical properties differentiation of the japonica varieties, although it did reveal an initial clue to the close relationship between Korean rice and the Japanese and Chinese varieties. Notably, these markers were also able to identify a premium japonica rice. The molecular markers and information concerning the genetic relationship would be useful in improving the japonica rice along with its starch quality of in breeding program.